PERJANJIAN BANGUN GUNA SERAH ANTARA PEMERINTAH KABUPATEN/KOTA DAN PERSEROAN TERBATAS - Urip Santoso (Mimbar Hukum - Fakultas Hukum Universitas Gadjah Mada, 2014)
Status of land that can be controlled by the local government is the right of use and the right of management. The right of management can be the object of Agreement on Build, Operate, and Transfer between the local government and the company. Then, the company gets the right of management through the Government Decision which is written up in to a form of Decree of Granting Rights. In the last term of the Agreement on Build, Operate, and Transfer, the land and the building with all support facilities submitted by company to the local government. Status tanah yang dapat dikuasai oleh pemerintah kabupaten/kota adalah hak pakai dan hak pengelolaan. Tanah yang berstatus hak pengelolaan pemerintah kabupaten/kota yang dapat menjadi objek Perjanjian Banguna Guna Serah dengan Perseroan Terbatas. Perseroan Terbatas mendapatkan hak guna bangunan atas tanah hak pengelolaan melalui Penetapan Pemerintah dalam bentuk Surat Keputusan Pemberian Hak. Pada akhir masa Perjanjian Banguna Guna Serah, tanah dan bangunan beserta sarana pendukungnya diserahkan oleh Perseroan Terbatas kepada pemerintah kabupaten/kota.